Monomeric nickel hydroxide stabilized by a sterically demanding phosphorus–nitrogen PN3P-pincer ligand: synthesis, reactivity and catalysis. Issue 45 (10th October 2018) - Yao, Changguang; Chakraborty, Priyanka; Aresu, Emanuele; Li, Huaifeng; Guan, Chao; Zhou, Chunhui; Liang, Lan-Chang; Huang, Kuo-Wei
Abstract : Various new nickel complexes and amides are synthesized using monomeric nickel hydroxide (PN 3 P)Ni(OH) (3 ) as the precursor or catalyst. Abstract : A terminal nickel hydroxide complex (PN 3 P)Ni(OH) (3 ) bearing the 2 nd generation phosphorus–nitrogen PN 3 P-pincer ligand has been synthesized and structurally characterized. As a nucleophile, 3 reacts with CO to afford the hydroxycarbonyl complex 4, (PN 3 P)Ni(COOH). 3 can also activate CO2 and CS2 to produce nickel bicarbonate (PN 3 P)Ni(OCOOH) (5 ) and bimetallic dithiocarbonate [(PN 3 P)NiS]2 CO (6 ) respectively, as well as to promote aryl isocyanate and isothiocyanate insertion into the Ni–OH bond to give the corresponding (PN 3 P)NiEC(O)NHAr complexes (E = O, 7 ; E = S, 8 ). In addition, 3 catalyzes the nitrile hydration to various amides with well-defined intermediates (PN 3 P)Ni–NHC(O)R (R = Me, 9 ; R = Ph, 10 ).